Faktor Risiko yang Berpengaruh terhadap Kejadian HIV/AIDS pada Pengguna Napza Suntik (Studi Epidemiologi Di Kota Pontianak) - Sumini Sumini; Suharyo Hadisaputro; Anies Anies; Budi Laksono; Muchlis AU Sofro (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2017)
Background: Injecting drug users (IDUs) are play role of high risk of HIV infection due to sexual behaviors that do not use condoms and use of unsterile needles. The high productive age group affected by HIV/AIDS and death, then the lower life expectancy, availability and productivity of the workforce. The purpose of the study proved that individual and environmental factors are risk factors for the incidence of HIV / AIDS among injecting drug users.Method: This observational analytic study, with the design of the case control study equipped with a qualitative approach of risk factors retrospectively. The target population of the study were IDUs in Pontianak with a sample of 96 people consisting of 48 cases of HIV/AIDS and 48 were IDUs not control HIV/AIDS. The sampling method is non-probability sampling study with consecutive sampling manner. Data analysis included univariate, bivariate using chi- square test and multivariate logistic regression test.Results: Multivariate analysis of four variables associated with the incidence of HIV/AIDSamong IDUs is married status (OR = 5,57), had sexual intercourse more than two people (OR =4,13), frequency of injecting drugs > 6 time / week yet (OR = 3,71), and not / do not work (OR= 3,28)Conclusion: Risk factors were shown to inﬂuence: the married status, had sexual intercourse more than ≥ 2 people, frequency of injecting drugs > 6 times / week and not/do not work yet.